2014
DOI: 10.1016/j.agsy.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Merging remote sensing data and national agricultural statistics to model change in irrigated agriculture

Abstract: a b s t r a c tOver 22 million hectares (ha) of U.S. croplands are irrigated. Irrigation is an intensified agricultural land use that increases crop yields and the practice affects water and energy cycles at, above, and below the land surface. Until recently, there has been a scarcity of geospatially detailed information about irrigation that is comprehensive, consistent, and timely to support studies tying agricultural land use change to aquifer water use and other factors. This study shows evidence for a rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 40 publications
(59 reference statements)
1
86
0
1
Order By: Relevance
“…The potential exists to develop annual updates of the MIrAD using year-specific MODIS and the USDA crop acreage statistics that reflect the yearly distribution of fields that are irrigated across large areas. Work has recently been completed to develop a 2007 MIrAD applying the same classification strategy to updated MODIS and the USDA Census data for that year and was shown by Brown and Pervez (2014) to be useful for detecting change in the spatial extent of irrigated agriculture. Pervez and Brown (2010) note that 2002 was a relatively dry year across most of the United States with persistent drought conditions over areas such as Nebraska, which provided an enhanced peak NDVI difference between irrigated and rainfed crops that was beneficial for discriminating these two land use classes.…”
Section: Discussionmentioning
confidence: 99%
“…The potential exists to develop annual updates of the MIrAD using year-specific MODIS and the USDA crop acreage statistics that reflect the yearly distribution of fields that are irrigated across large areas. Work has recently been completed to develop a 2007 MIrAD applying the same classification strategy to updated MODIS and the USDA Census data for that year and was shown by Brown and Pervez (2014) to be useful for detecting change in the spatial extent of irrigated agriculture. Pervez and Brown (2010) note that 2002 was a relatively dry year across most of the United States with persistent drought conditions over areas such as Nebraska, which provided an enhanced peak NDVI difference between irrigated and rainfed crops that was beneficial for discriminating these two land use classes.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, irrigation classification is essentially an arduous procedure since the phenological difference in vegetation canopy is subtle for classification schemes to reliably detect the spectral difference between irrigated and non-irrigated surfaces. Several studies (e.g., [10,12,21]) have determined that the most widely used classification schemes are based on vegetation indices that are only spectrally sensitive to phenological variation under severe conditions such as droughts or desert climate. In this study, the proposed dual index scheme assimilates ETRF (scaled by GI), a phenological and soil water stress index [48] that is sensitive to short and long term water sufficiency or deficiency.…”
Section: Application In Humid To Arid Climate Regimes and Wet To Drymentioning
confidence: 99%
“…NDVI has been widely used as an important vegetation and irrigation monitoring tool [8,11,12,[20][21][22]. GI on the other hand, has been a less exploited vegetation index, yet studies [23,24] have found the index more sensitive to chlorophyll than NDVI, Enhanced Vegetation Index (EVI) [25], and Wide Dynamic Range Vegetation Index (WDRVI) [26].…”
Section: Normal Difference Vegetation Index and Green Indexmentioning
confidence: 99%
“…This effort focused only on grass and non-irrigated cropland, as determined by Brown and Pervez [63], to exclude the substantial production advantages that come with irrigation. To assess normality (a requirement for the application of classical statistics) in regional NEP distributions several approaches were applied: visual inspection of NEP regional frequency plots and the differences between mean and median regional NEP indicated skewness.…”
Section: Grass Versus Crop Nep Comparisonmentioning
confidence: 99%
“…This effort focused only on grass and non-irrigated cropland, as determined by Brown and Pervez [63], to exclude the substantial production advantages that come with irrigation.…”
Section: Grass Versus Crop Nep Comparisonmentioning
confidence: 99%